2021
DOI: 10.1126/science.aba2374
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Engrailed-1 activation in fibroblasts yields wound regeneration without scarring

Abstract: Skin scarring, the end result of adult wound healing, is detrimental to tissue form and function. Engrailed-1 lineage–positive fibroblasts (EPFs) are known to function in scarring, but Engrailed-1 lineage–negative fibroblasts (ENFs) remain poorly characterized. Using cell transplantation and transgenic mouse models, we identified a dermal ENF subpopulation that gives rise to postnatally derived EPFs by activating Engrailed-1 expression during adult wound healing. By studying ENF responses to substrate mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
272
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(280 citation statements)
references
References 42 publications
5
272
3
Order By: Relevance
“…Many cell surface and lineage markers have been associated with fibroblasts involved in wound healing, including Pdgfra , Engrailed-1 ( En1 ), and CD26 ( Dpp4 ) ( 22 24 ). However, we and others have found expression of such markers to be variable throughout wound tissue ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cell surface and lineage markers have been associated with fibroblasts involved in wound healing, including Pdgfra , Engrailed-1 ( En1 ), and CD26 ( Dpp4 ) ( 22 24 ). However, we and others have found expression of such markers to be variable throughout wound tissue ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S10 E ). To further explore these differences, we employed an automated feature extraction algorithm ( 24 ) to quantify ultrastructure characteristics of wound tissue sections, which demonstrated that FAK i -treated wound specimens were more similar to unwounded skin than to vehicle-control wounds, including for both mature and immature collagen fiber intensities ( SI Appendix , Fig. S10 F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using genetic lineage tracing, anatomical fate mapping, and live imaging, we found that fascia-resident fibroblasts orchestrate the mobility of the connective tissue into wounds. Fascial mobility is directed by a single fibroblastic cell lineage termed Engrailed-1 lineage positive fibroblasts (EPFs), which is the profibrotic lineage fibroblasts responsible for skin scarring [47][48][49]. This specialized fibroblast type physically drags the fascia into the wound bed and subsequently into the skin surface in mice (Figure 2a).…”
Section: Wound Repair By Subcutaneous Fasciamentioning
confidence: 99%
“…With increasing understanding of the complex roles YAP/TAZ play in lung development, homeostasis, injury repair, and pathologic fibrosis, it has become clear that approaching this pathway in a therapeutic context will not be as simple as global inhibition or activation, in contrast to other organs ( 51 ). While aberrant YAP activation in the epithelium and mesenchyme contribute to failure of repair, initial YAP activation in these cells is likely beneficial for proliferation of progenitor populations and signaling to immune cells ( 12 ).…”
Section: Future Work and Open Questionsmentioning
confidence: 99%